Pretreatment elevated erythrocyte sedimentation rate and C-reactive protein as a predictor of malarial complications - Vemula, Sachin; Katara, Vidyalakshmi; Bhaskaran, Unnikrishnan; Adappa, Sushma; Chakrapani, Mahabala (The Journal of Infection in Developing Countries, 2016)
Introduction: Complications of malaria can develop suddenly and unexpectedly. Although various parameters have been associated with severity of malaria, they have not been studied as predictors of these events. Many of the malarial complications are inflammatory in nature, and C-reactive protein (CRP) and elevated erythrocyte sedimentation rate (ESR) could be early markers of these complications and might precede and predict the development of complications. Methodology: A total of 122 inpatients with uncomplicated newly diagnosed malaria were studied. CRP, ESR, hemoglobin, and platelets were measured before initiating treatment. Patients were monitored closely for the subsequent development of complications based on the World Health Organization’s definition of severe malaria. Results: Seven patients (5.7%) had worsening of symptoms compared to the day of admission and had higher pretreatment CRP and increased ESR compared to those patients who did not develop complications. Area under receiver operator characteristic curve was 0.761(p=0.02) for CRP and 0.739 (p = 0.035) for ESR. CRP>124 mg/L and increased ESR (>34.5 mm in the first hour) had a sensitivity of 71.4% and specificity of 79.1%, respectively, for predicting complications of malaria. Other parameters did not reach statistical significance for predicting complications. Elevated CRP and elevated ESR had a negative predictive value of 97.8%. Conclusions: Elevated CRP>124mg/L and increased ESR>34.5 mm in the first hour at the time of diagnosis in patients with uncomplicated malaria identifies patients who might subsequently develop complications of malaria.